A Study on the Gap Areas in Ecotourism Planning, Policy Implications and Initiatives in Kerala - Mathew, Ravish; Chandran, Anu (Atna Journal of Tourism Studies, 2010)
It is an unvarnished fact that Ecotourism is a niche segment in God's own Country, which is ardently subscribed by tourists from across the globe. Kerala boasts of rich, diverse and potent natural resources ideally suited for ecotourism promotion. The positive attributes of ecotourism was realized by destination planners and designers of the state, especially its remarkable potential to foster sensitivity towards the environment. The accentuation of eco tourism in Kerala is credited with numerous beneficial impacts for tourists, host communities and environments including conservation, promotion of positive environmental ethics, sustainable development opportunities, environmental education(which is the central characteristic of eco tourism,) and revenue to the government that helps to implement management protection systems. Kerala has pioneered novel concepts and practices in the realm of tourism and in the process, this renowned tourist destination was showered with accreditations from numerous global institutions and agencies. It obviously mattered a lot when the state drafted an ecotourism policy, clearly stream lining the action plan. Then mala an idyllic tourist spot situated in southern Kerala is recognized as the first planned ecotourism destination in India. It also bagged several international awards including the coveted PATA award for the best eco tourism project. Similar projects were incepted and EIA's were conducted across the eco tourism spots as an off shoot of the Policy decisions. Yet, the eco tourist destinations in the state experience certain travails that pose constraints in the smooth operation of eco tourism. This paper elucidates on those factors both tangible and intangible that create hurdles in the path of sustainable eco tourism promotion in Kerala. The effort is directed to bring to light the grey areas that fail the eco tourism goals. The nuances of eco tourism planning are studied in this work with reference to the major recognized eco tourism destinations of Kerala and the efficiency of ecotourism projects. A model is also proposed in the study on pragmatic ecotourism management in the Kerala context.